Relevant market delineation and horizontal merger simulation: A unified approach - Eduardo P. S. Fiuza (Institute for Applied Economic Research (ipea), 2015)
While often times the Hypothetical Monopolist Test (HMT) utilized in relevant market delineation is implemented with uniform price increases throughout all the goods in the candidate relevant market, since 1984 the versions of the U.S. Merger Guidelines have emphasized that these small but significant and non-transitory increase in prices (SSNIP) should be profit-maximizing, what would result in uniform increases only under very particular conditions. Such increases could then be analyzed - sufficient data existing for such - in the same manner as the simulations of unilateral effects of mergers, introduced in the 1980s and further developed in the 1990s. Thus, in this article, building on structural models of demand and supply and on recent contributions to the literature, we propose a unified framework for merger simulations and for the so-called HMT in its diversity of versions implemented in various countries along the years, and we better detail their differences. To illustrate those differences, we report the results of a Monte Carlo experiment using three demand specifications: isoelastic, linear and linearized Almost Ideal Demand System (AIDS), all of them in a two-stage budget setting. We conclude that the choice of the test version and of the demand specification may affect significantly the size of the relevant market found, depending on the distribution and magnitude of cross and own price elasticities in the potential market.
Keywords: L40; L13; L11; 330